2016
DOI: 10.1111/jace.14242
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Calcium Silicate Hydrate in Highly Alkaline System

Abstract: Synthesis of calcium silicate hydrate (C-S-H) was conducted over the range of 50°C-90°C and C/S ratio of 0.86-2.14 in the highly alkaline Na 2 O-CaO-SiO 2 -H 2 O system for silicon utilization in high alumina fly ash. Structural change in C-S-H formed in the highly alkaline system was investigated using XRD and 29 Si MAS NMR spectra. X-ray photoelectron spectroscopy was used to confirm the amount of sodium ions in C-S-H. Conversion of Si may reach 99% under optimum conditions. A higher degree of polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The main reaction product for these cements, an amorphous gel or gels (actually a mix of cementitious gels) appeared on the diffractograms as a hump stretching from 25° to 35° (2θ). According to the literature, the presence of a certain amount of alkalis can accelerate initial calcium silicate hydration from PC, favoring the precipitation of portlandite and C‐S‐H gel. The ash reacted well with the Ca(OH) 2 or with the alkalis to generate more cementitious gel that took Al and Na up into its structure, forming C‐(N)‐A‐S‐H‐like gels (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…The main reaction product for these cements, an amorphous gel or gels (actually a mix of cementitious gels) appeared on the diffractograms as a hump stretching from 25° to 35° (2θ). According to the literature, the presence of a certain amount of alkalis can accelerate initial calcium silicate hydration from PC, favoring the precipitation of portlandite and C‐S‐H gel. The ash reacted well with the Ca(OH) 2 or with the alkalis to generate more cementitious gel that took Al and Na up into its structure, forming C‐(N)‐A‐S‐H‐like gels (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, high temperature could promote the reaction speed of C-S-H formation, but meanwhile, impurities would be generated. Generally, heating at high temperature is a common method to produce C-S-H [28,29]. However, from the view of engineering application, RTC-S-H is a more promising material for environmental applications because much more energy could be saved when synthesized at room temperature than that of heating at high temperature.…”
Section: Characterizationsmentioning
confidence: 99%
“…C‐S‐H is commonly synthesized through calcium oxide and silica fume or chemical grade silicon source as sodium silicate with calcium source of calcium nitrate under lower temperature and the research cycle is in a quite long time. Our previous studies have shown that C‐S‐H can be successfully synthesized in model solution, whose structure and components depend on many factors such as Ca/Si and temperature 20 . The thus‐synthesized C‐S‐H shows a potential prospect to be applied as seeds to accelerate cement hydration and as absorbent material for heavy metals in wastewater 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that C-S-H can be successfully synthesized in model solution, whose structure and components depend on many factors such as Ca/Si and temperature. 20 The thus-synthesized C-S-H shows a potential prospect to be applied as seeds to accelerate cement hydration and as absorbent material for heavy metals in wastewater. 21,22 This research endeavors to obtain high-efficiency utilization for real DSS generated from the pretreatment process of HAFA.…”
Section: Introductionmentioning
confidence: 99%